Health care financing by non‐governmental sector in India. Issue 3 (25th August 2020) - Das, Nimai; Selvaraj, Sakthivel; Kumar, Rajeev
Abstract : The non‐governmental but non‐profit organisations seem to have occupied a critical space in financing and delivery of health care services at societal needs with limited but critical resources to bridge the gap between deficiency in public sector facilities and unaffordability of for‐profit operations. Present study based on a national level primary survey of non‐governmental sector in India finds that they are imperative in filling the void, especially providing preventive and promotive health care services. It is observed that this sector contributed around 2.1% of overall health financing in country with a wide variation across subnational states. These organisations generate resources largely from the governments and development partners to facilitate achieving key goals and deliver outcomes to targeted beneficiaries.